Is Glasgow prognostic score a predictor of mortality in infective endocarditis? - Emlek, Nadir; Özyıldız, Ali Gökhan; Şahin, Müjgan Ayşenur; Ergül, Elif; Aydın, Cihan (The European Research Journal, 2022)
Objectives: The inflammation-based Glasgow prognostic score (GPS), which comprises elevated serum C-reactive protein (CRP) and decreased albumin concentration, is the most valid inflammatory risk score in cancer. New prognostic markers are needed to predict high-risk infective endocarditis (IE) patients. In the present study, we investigated the in-hospital mortality estimation of GPS in infective endocarditis patients. Methods: The retrospectively designed study included 53 IE patients diagnosed according to Duke criteria. Demographic and clinical data of the patients were recorded and GPS levels were measured. Patients were divided into two groups according to in-hospital mortality outcomes. Glasgow prognostic score was rated as 0, 1, or 2 points based on serum albumin and C-reactive protein levels. Results: The nonsurvivor group was older and the number of patients with kidney failure or diabetes was higher in this group. Glasgow prognostic score was higher in the nonsurvivor group, while albumin levels were lower. Thirty-four patients died during intensive care unit follow-up, and the mean follow-up period was 24.1 ± 18.6 days. ROC analysis showed that the Glasgow prognostic score had a sensitivity of 82.4% and a specificity of 36.8% at a cut-off value of ≥1.5 in predicting in-hospital mortality. Chronic renal failure (OR: 6.720; 95% CI: 1.907-23.684; p = 0.003) and age (OR: 1.040; 95% CI: 1.001-1.081; p = 0.044) were the independent variables of the mortality prediction in univariate logistic regression analysis. In multivariate logistic regression analysis, only chronic renal failure (OR: 0.153; 95% CI: 0.036-0.653; p = 0.011) was found to be a significant predictor of mortality. Kaplan–Meier survival analysis revealed that long-term survival was reduced in patients with a high GPS (Log-rank: p = 0.003). Conclusions: Glasgow prognostic score level is associated with increased in-hospital mortality in IE patients. Chronic renal failure and GPS are the independent predictors of mortality.